Localized mesosphere-stratosphere-troposphere radar echoes from the E region at 69 degrees N: Properties and physical mechanisms - Rapp, Markus; Leitert, Lasse; Latteck, Ralph; Zecha, Marius; Hoffmann, Peter; Höffner, Josef; Hoppe, Ulf-Peter; La Hoz, Cesar; Thrane, Eivind (Journal of Geophysical Research: Space Physics, 2011)
We present the first observations, to our knowledge, of a new class of high‐latitude mesosphere‐stratosphere‐troposphere radar echoes from the E region as observed with the Arctic Lidar Observatory for Middle Atmosphere Research wind radar during the period 2004–2008. These echoes occur primarily during the summer months and in the altitude range from 93 to 114 km, with a pronounced peak of maximum occurrence at about 100 km. The echoes are rather short with typical durations of ∼20 min, with some examples lasting as long as 3 h. The echoes typically cover only a few hundred meters in the vertical and show both small Doppler velocities (±1–2 m/s) as well as very narrow spectral widths (just a few meters per second when converted to Doppler velocities). The echoes are highly aspect sensitive indicative of a specular‐scattering mechanism and reveal a distinct diurnal variation with maxima of occurrence around noon and midnight. The latter is related to the semidiurnal tidal components of the zonal and meridional wind where times of occurrence correspond to large values of corresponding vertical wind shears. Considering possible physical mechanisms, turbulence with large Schmidt number scatter is likely ruled out as is auroral backscatter. Finally, a strong case for a close correspondence of the echoes to sporadic E layers is presented on the basis of comparisons to ionosonde data, occurrence patterns of sporadic layers, simultaneous and common volume lidar measurements of a sporadic Fe layer, as well as simultaneous measurements of sporadic E layers with the European Incoherent Scatter UHF radar at a horizontal distance of 130 km. Applying the theory of partial reflections to the observed electron density gradients, we are able to demonstrate that the observed echo strengths can likely be explained on the basis of this scattering mechanism.